Enhancing Our Understanding of Teachers' Personal Responsibility for Student Motivation: A Mixed Methods Study - Daniels, Lia M.; Poth, Cheryl; Goegan, Lauren D. (Frontiers in Education, 2018)
As measured by the Teachers Responsibility Scale, teachers appear to have surprisingly low levels of personal responsibility for student motivation even though they qualitatively identify low student motivation as a major teaching concern. Thus, the purpose of the current mixed methods research was to compare the way teachers’ respond to items about personal responsibility for student motivation quantitatively and qualitatively. We used a convergent sequential mixed method design to answer the following research question: How do practicing teachers’ perceptions and experiences of being personally responsible for student motivation converge with a quantitative measure of the construct? One hundred and 80 practicing teachers completed a self-report questionnaire on personal responsibility and then six teachers were purposefully sampled to participate in small-group interviews sharing their perspectives on responsibility for motivation specifically. The quantitative and qualitative data were analyzed separately and then integrated through a qualitative dominant crossover mixed analyses. Five mixed insights emerged and are represented in a joint display: dominance of interest, shared responsibility, divergent specificity and valence, complete alignment, and missingness of professional perspective. The mixed insights have important implications for theory, research, and practice and highlight the contribution that mixed methods can have in advancing motivation research.